Community assembly during vegetation succession after metal mining is driven by multiple processes with temporal variation. Issue 5 (29th April 2022) - Li, Ting; Yang, Huaju; Yang, Xinting; Guo, Zhaolai; Fu, Denggao; Liu, Chang'e; Li, Shiyu; Pan, Ying; Zhao, Yonggui; Xu, Fang; Gao, Yang; Duan, Changqun
Abstract: The mechanisms governing community assembly is fundamental to ecological restoration and clarification of the assembly processes associated with severe disturbances (characterized by no biological legacy and serious environmental problems) is essential. However, a systematic understanding of community assembly in the context of severe anthropogenic disturbance remains lacking. Here, we explored community assembly processes after metal mining, which is considered to be a highly destructive activity to provide insight into the assembly rules associated with severe anthropogenic disturbance. Using a chronosequence approach, we selected vegetation patches representing different successional stages and collected data on eight plant functional traits from each stage. The traits were classified as establishment and regenerative traits. Based on these traits, null models were constructed to identify the processes driving assembly at various successional stages. Comparison of our observations with the null models indicated that establishment and regenerative traits converged in the primary stage of succession. As succession progressed, establishment traits shifted to neutral assembly, whereas regeneration traits alternately converged and diverged. The observed establishment traits were equal to expected values, whereas regenerative traits diverged significantly after more than 20 years of succession. Furthermore, the available Cr content was linked strongly to species' ecological strategies. In the initial stages of vegetation succession in an abandoned metal mine, the plant community was mainly affected by the available metal content and dispersal limitation. It was probably further affected by strong interspecific interaction after the environmental conditions had improved, and stochastic processes became dominant during the stage with a successional age of more than 20 years. Abstract : Based on the functional traits of plants, the assembly rules of the early and middle stages of vegetation succession were revealed. It provides theoretical basis for restoration activities after serious disturbance.